Práticas de qualidade na integração da cadeia de suprimentos e seus impactos sobre o desempenho: uma ótica sobre a practice-based-view (PBV) - Carvalho, Julia Pinto de (2018)
The supply chain integration (SCI) deals with the strategic collaboration between internal organizational processes and between members of a supply chain. Several studies conducted since the beginning of the new millennium shows the importance of integrating internal practices with suppliers and external customers. Supply Chain Quality Management (SCQM) increases the adoption of practices previously directed towards company and product, highlighting the importance of integrating supply chain members, with the goal of continuous quality improvement of products, services or processes. Although there are numerous studies that emphasize practices of quality and integration simultaneously in the elaboration of their constructs, they do not investigate how these concepts relate to each other. And while there have been recent studies that quantify the relationship between integration and quality practices, none of them have evaluated the effect of integration with regard to mediating the relationship between quality and performance practices. Therefore, this research’s main research question deals with how the different levels of supply chain integration affect the performance results originated from the adoption of quality practices. In other to answer this question, this research will be based on practice-based-view (PBV) and adopt qualitative and quantitative methods. It will use a meta-analysis, a quantitative method to combine data from quality and performance practices. Survey results measured how these practices, moderated by different levels of integration, impact performance. Finally, it was identified via semistructured interviews how the adoption of different quality practices interferes at different levels of integration. The meta-analysis mapped 562 correlations in 38 articles covering 16.333 sample units. It shows the correlation between the adoption of quality practices and organizational performance to be 0.182 and 0.242 for organizational and operational performance, respectively. The results of a survey applied to quality and supply chain managers and leaders revel that integration has a significant moderating effect on the relationship between the adoption of quality practices and operational performance. In general, higher levels of integration present better performance results. In other words, when the company integrates only internally, performance results can lead to loss. The effect tends to decrease as the level of integration rises. A significant effect from the leader's experience was also identified. Finally, a total of 22 semi-structured interviews reveal that more often than expected, the integration of quality practices is developed by necessity, such as when a company needs to access its supply chain to solve a specific quality problem related to a product or a raw material, or when a company is required to disclose quality levels through certifications in order to be able to close contracts with key customers which will bring significant gains to the company’s performance. As integration advances, it has the potential to be assimilated into the company’s culture, thereby establishing an integrative routine from which partners are able to learn through daily exchange of information, in turn leading to new opportunities for continuous improvement. Finally, the research shows innovation to be a mediator factor in the relation and integration between quality practices and performance, which will be crucial to direct future research.